Prediction of central location of the state with irregular boundary (2011)
"Mathematics has diverse applications as decision making tool. This study investigated the use of a proposed pure mathematical formulation (i.e. excluding human factor) for citing appropriately the location of political capital ci of an inhabited designated area. Digitized data of Scale map of Nigeria as a case study was used as input to a FORTRAN 90 programme codes of an equivalent least squares method mathematical formulation. The resulting simultaneous equations involving the political capital city coordinates as unknown variables were solved using Gauss Elimination Algorithm. The political capital city Cartesian coordinate prescribed as (26, 24) in grids unit for the studied case of scale map of Nigeria compared visually satisfactorily with Abuja location on the Map. The Nigeria land area cover was under-estimated by 2.3% referencing 923,768 sq km obtained from Microsoft Encarta Premium (2009). Similarly the Nigeria coastline was estimated. as 25.3% of the country's estimated perimeter (3369 krn). This mathematical tool can be used to cite the centrally located capital city or capital city relocations economically, timely, accurately and reliably. This programme can also be used for citing of capital cities for other countries and center of any irregular shapes on two dimensional plane. "